Moznosti a výsledky chirurgického riesenia benígnej tracheoezofageálnej fistuly - Krajc, T; Janík, M; Lucenic, M; Benej, R; Harustiak, S (Rozhledy v chirurgii, 2010)
AIM: Review of literature and a single-institution retrospective analysis of possibilities and results of various surgical techniques in treatment of benign tracheoesophageal fistula (TEF). MATERIAL AND METHODS: Between 1995 and 2010, 26 patients with benign tracheoesophageal fistula of various etiology underwent surgical treatment at the Department of Thoracic Surgery of Slovak Medical University and Faculty Hospital in Bratislava. The majority of patients had a postintubation TEF (21 cases), two fistulas were of traumatic origin, one iatrogenic, one congenital with adulthood manifestation and one tracheo-neoesophageal (TNEF) following an esophagectomy for carcinoma via extended cervical approach with lymphadenectomy and sternal retraction adpoted from transcervical extended mediastinal lymphadenectomy. We review the possible means of surgical treatment of TEF, of which we most frequently used segmental tracheal resection with end-to-end anastomosis and a non-overlying suture of the esophageal defect without muscle flap interposition (16 patients), transsection of the fistula with muscular flap interposition via cervical (2 patients) or transthoracic (1 patient) approach; or a T-tube insertion with (1 patient) or without (5 patients) discision and suture of the TEF. The only tracheo-neoesophageal fistula in our experience had been treated by neoesophagectomy, covering of tracheal defect by intercostal muscle flap and cervical esophagostomy. RESULTS: Short- and long-term results of TEF treatment in our institution have been favourable, with perioperative mortality of 3.8% (the patient with tracheo-neoesophageal fistula). Morbidity included 1 partial tracheal anastomotic dehiscence, 3 temporary left recurrent nerve palsies, temporary deglutition disorders (15 patients), tracheal anastomosis granulations in 1 patient and 2 wound infections. Out of 26 patients 15 (58%) are being followed-up on a regular basis, all with good (12 patients) or satisfactory (3 patients) functional results. CONCLUSION: In the paper we analyze the advantages and disadvantages of various techniques and their alternatives in the treatment of TEF. As the most reliable and suitable solution for patients with postintubation TEF, breathing spontaneously and with acceptable nutritional status, we favour segmental trachea resection with end-to-end anastomosis and esophageal suture without muscle interposition, regardless of presence of concomitant tracheal stenosis. Fistulae of other etiologies require diverse approaches, especially tailored with respect to their location. Management of tracheo-neoesophageal fistula following esophagectomy for carcinoma is extremely demanding. Therefore, it is crucial to adhere to basic rules of prevention of such benign but potentially fatal entities as TEF and TNEF.
Keywords: hrudní chirurgické výkony; Humans; ženské pohlaví; Intubation, Intratracheal; Tracheoesophageal Fistula; mužské pohlaví; trachea; Trachea; Male; Esophagus; mladý dospělý; senioři; lidé; Young Adult; Thoracic Surgical Procedures; tracheoezofageální píštěl; Aged; intratracheální intubace; ezofágus; Female